2016
DOI: 10.1099/ijsem.0.001272
|View full text |Cite
|
Sign up to set email alerts
|

Geodermatophilus pulveris sp. nov., a gamma-radiation-resistant actinobacterium isolated from the Sahara desert

Abstract: A black-pigmented, aerobic actinobacterium, tolerant to ionizing radiation, designated BMG 825 T , was isolated from desert limestone dust in Tunisia. The strain grew within the temperature range 10-40 C, at pH 5.5-11.0 and in the presence of 2 % NaCl. The DNA G+C content was 75.7 mol%, and its cell-wall peptidoglycan contained meso-diaminopimelic acid. Sugars of whole-cell hydrolysates were galactose, glucose, and trace amounts of ribose and mannose. The predominant menaquinone was MK-9(H 4 ), and the major f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…It is in accordance with patterns obtained for the closely related species investigated in this study ( Figures 3b–d ) and the phospholipid pattern revealed by Bertazzo et al (2014) for G. brasiliensis . The randomForest analysis detected the lack of phosphatidylcholine and the presence of glycophosphatidylinositol as excellently predictive of the prospective new genus, whereas the absence of phosphatidylglycerol was also observed in other Geodermatophilus species ( Bertazzo et al, 2014 ; Montero-Calasanz et al, 2014b , 2015 ; Hezbri et al, 2015a , b , c , 2016a ). The unambiguous presence of hydroxyphosphatidylethanolamine is a slightly less relevant taxonomic marker for the prospective new genus; among core Geodermatophilus it was only detected in the polar lipid profile of G. pulveris DSM 45839 T by Hezbri et al (2016a) .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is in accordance with patterns obtained for the closely related species investigated in this study ( Figures 3b–d ) and the phospholipid pattern revealed by Bertazzo et al (2014) for G. brasiliensis . The randomForest analysis detected the lack of phosphatidylcholine and the presence of glycophosphatidylinositol as excellently predictive of the prospective new genus, whereas the absence of phosphatidylglycerol was also observed in other Geodermatophilus species ( Bertazzo et al, 2014 ; Montero-Calasanz et al, 2014b , 2015 ; Hezbri et al, 2015a , b , c , 2016a ). The unambiguous presence of hydroxyphosphatidylethanolamine is a slightly less relevant taxonomic marker for the prospective new genus; among core Geodermatophilus it was only detected in the polar lipid profile of G. pulveris DSM 45839 T by Hezbri et al (2016a) .…”
Section: Resultsmentioning
confidence: 98%
“…The properties are as given in the species description by Hezbri et al (2016a) with the following modification. The genomic G+C content is 75.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recent surge in the number of Geodermatophilus species the genus remains underspeciated [18][19][20]. Geodermatophilus strains tend to be associated with soils, notably desert soils [1,16,[21][22][23][24][25][26][27][28][29][30] though there is evidence that they are more widely distributed in the environment [15,30,31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Phenotypic properties that differentiate Geodermatophilus chilensis isolates. B12 T , B20 and B25 from closely related type-strains of the genus Geodermatophilus.Strains: 1, B12 T , B20 and B25 (data from this study); 2, G. africanus DSM 45422 T[58]; 3, G. obscurus DSM 43160 T (data from this study, unless indicated); 4, G. poikilotrophus DSM 44209 T[64,73]; 5, G. pulveris DSM 46829 T[79]; 6, G. ruber DSM 45317 T[55]; 7, G. sabuli DSM 46844 T[31]; 8, G. siccatus DSM 45419 T[29].…”
mentioning
confidence: 99%